MHD Eyring–Powell nanofluid flow across a wedge with convective and thermal radiation - Raju, CH. Narasimha; Reddy, C. Srinivas; Alyami, Maryam Ahmed; Eldin, Sayed M; Adnan,; Asogwa, Kanayo Kenneth; Pushpa, D.; Dharmaiah, V. (Frontiers in Energy Research, 2022)
The heat transport of the Eyring-Powell nanomaterial boundary layer flow on a wedge surface with passively controlled nanoparticles was theoretically studied in this paper. The boundary condition of thermal convection is considered. The considered model predicts the characteristics of a non-Newtonian Eyring-Powell fluid. The features of thermophoresis due to thermal gradient and Brownian motion due to nanoparticles were discussed using the Buongiorno model. The prevailing nonlinear boundary layer equations are derived and then renewed in an ordinary differential boundary value problem (ODBVP) by substituting apt similarity transformations. The acquired nonlinear ODBVP is then resolved using the bvp4c method to explore the fields of nanofluid velocity, nanofluid temperature, and nanoparticle concentration. A mathematical examination of the surface drag force coefficients and Nusselt number was carried out using various physical parameters. The Eyring-Powell fluid parameter reduces the thickness of the momentum boundary layer thickness. The thermophoresis aspect enhances the thermal field and solutal field. The Nusselt number reduces the need for a stronger internal heat source mechanism.